2008
DOI: 10.1134/s1054660x08010015
|View full text |Cite
|
Sign up to set email alerts
|

Rotating trapped Bose-Einstein condensates

Abstract: After reviewing the ideal Bose-Einstein gas in a box and in a harmonic trap, I discuss the effect of interactions on the formation of a Bose-Einstein condensate (BEC), along with the dynamics of small-amplitude perturbations (the Bogoliubov equations). When the condensate rotates with angular velocity Ω, one or several vortices nucleate, with many observable consequences. With more rapid rotation, the vortices form a dense triangular array, and the collective behavior of these vortices has additional experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
186
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(190 citation statements)
references
References 164 publications
(358 reference statements)
3
186
0
1
Order By: Relevance
“…They are well-known objects, studied in detail theoretically and created in experiments, prior to the work on bright vortex solitons. Results obtained for the "dark vortices", starting from the earliest ones [86][87][88], have been collected in many publications dealing with various settings in photonics [89][90][91][92][93][94][95] (including exciton-polariton condensates [96][97][98], where the vortices exist in dissipative media) and BEC [61,[99][100][101][102][103][104][105], as well as in quantum Fermi gases [106,107]; see also book [108] for an overview of the theme. The studies of vortices in this context are also known as "singular optics", with pivots of the vortices considered as singularities of optical fields; many publications on the latter theme were collected in a special issue of Journal of Optics [109] (see also book [110]).…”
mentioning
confidence: 99%
“…They are well-known objects, studied in detail theoretically and created in experiments, prior to the work on bright vortex solitons. Results obtained for the "dark vortices", starting from the earliest ones [86][87][88], have been collected in many publications dealing with various settings in photonics [89][90][91][92][93][94][95] (including exciton-polariton condensates [96][97][98], where the vortices exist in dissipative media) and BEC [61,[99][100][101][102][103][104][105], as well as in quantum Fermi gases [106,107]; see also book [108] for an overview of the theme. The studies of vortices in this context are also known as "singular optics", with pivots of the vortices considered as singularities of optical fields; many publications on the latter theme were collected in a special issue of Journal of Optics [109] (see also book [110]).…”
mentioning
confidence: 99%
“…The GP equation and its vortex solutions is a subject of its own that can be studied independently of the many-body problem. See the monograph [13] and the review article [14] where a large number of references can be found. The most detailed results are for the two-dimensional GP equation, i.e.…”
Section: The General Settingmentioning
confidence: 99%
“…is no longer bounded below [28], see also [14] for a review. As Ω c − Ω → 0 + the effective radius R of the condensate tends to infinity and the system becomes effectively two-dimensional.…”
Section: Remarks On Rapid Rotation In Harmonic Trapsmentioning
confidence: 99%
“…A major research track within this broad theme concerns the nonlinear properties of the solitary waves supported by the weakly interacting gas, sharing many similarities with nonlinear optics [3]. In this context, a large variety of solitary waves has been studied in the context of BECs, ranging from dark solitons [4], vortices and vortex lines [5,6], vortex rings [7] to more complex vortical structures such as long-lived knots [8]. On the other hand, the creation of fermionic and multicomponent condensates is believed to be useful for understanding the high-temperature superconductivity [9].…”
Section: Introductionmentioning
confidence: 99%